2021
DOI: 10.4103/aja.aja_82_20
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections and implications for male reproductive health

Abstract: Viral infections have haunted humankind since times immemorial. Overpopulation, globalization, and extensive deforestation have created an ideal environment for a viral spread with unknown and multiple shedding routes. Many viruses can infect the male reproductive tract, with potential adverse consequences to male reproductive health, including infertility and cancer. Moreover, some genital tract viral infections can be sexually transmitted, potentially impacting the resulting offspring's health. We have summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 210 publications
(296 reference statements)
0
22
1
1
Order By: Relevance
“…42 Other viruses may also induce orchitis, primarily systemically, including dengue, coxsackie, rubella, echovirus, and influenza viruses. 26 As mentioned, testicular changes in COVID-19 are similar to those observed in SARS 20 ; inflammatory changes that decrease spermato-genesis and hormonal production due to Leydig cell loss. The works of Yang et al, 23 20 These studies also reported the loss of spermatogonia through apoptosis [21][22][23] , the presence of SARS-CoV-2 antigen in interstitial and intratubular cells, 22 and viral particles by EM.…”
Section: Discussionmentioning
confidence: 63%
“…42 Other viruses may also induce orchitis, primarily systemically, including dengue, coxsackie, rubella, echovirus, and influenza viruses. 26 As mentioned, testicular changes in COVID-19 are similar to those observed in SARS 20 ; inflammatory changes that decrease spermato-genesis and hormonal production due to Leydig cell loss. The works of Yang et al, 23 20 These studies also reported the loss of spermatogonia through apoptosis [21][22][23] , the presence of SARS-CoV-2 antigen in interstitial and intratubular cells, 22 and viral particles by EM.…”
Section: Discussionmentioning
confidence: 63%
“…This is a pertinent finding as it shows that no carrier state is found in COVID-19 patients in semen. Several viruses (Human immune deficiency virus, hepatitis B Virus, Ebola virus, human papillomavirus and herpes simplex virus) are known to establish a chronic state and are transmitted sexually (Teixeira et al, 2021). On the contrary, shedding of the Zika virus in semen was found almost 70 -132 days after the symptom onset (Huits et al, 2017), yet sexual transmission has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of ACE-2 receptors on the testis has been cited as a potential source of infection of the testis by SARS-CoV-2, the evidence regarding the COVID-19 affliction of testis directly is controversial. Presently, the affliction of testis could be attributed to an indirect immune-mediated reaction, as established by the autopsy studies (Hallak et al, 2021;Teixeira et al, 2021). The COVID-19 pandemic also hit the assisted reproduction facilities due to uncertainties over the transmission of virus through semen and its effect on embryo and pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Blood-testis barrier and blood-epididymis barrier effectively guard the male reproductive tract, but a broad range of viruses can still breach these barriers and have been identified in semen (Salam and Horby, 2017;Teixeira et al, 2021). The persistence of the virus in semen has several implications.…”
Section: Sexual Transmissibility Of Rna Virusesmentioning
confidence: 99%
“…The presence of viruses may also affect semen characteristics and, thus, fertility. It should be noted that merely detecting a virus in semen does not imply that it is sexually transmissible, but epidemiologically, it is a critical public concern and needs to be informed whether the virus can be transmitted sexually, and mainly if the virus can be transmitted sexually by an asymptomatic individual, or fully recovered, or during the infection (incubation period) (Pike et al, 2021;Teixeira et al, 2021).…”
Section: Sexual Transmissibility Of Rna Virusesmentioning
confidence: 99%